Toward an Improved Meningococcal Serogroup B Assay - Jan Poolman (American Society for Microbiology, 2018)
ABSTRACT Because of diverse sequences and differential expression of surface structures on individual invasive Neisseria meningitidis serogroup B (MenB) strains, predicting the efficacy of MenB vaccines using traditional human serum bactericidal assays (hSBA) is impractical. The meningococcal antigen surface expression (MEASURE) assay uses flow cytometry to quantitate the expression of factor H binding proteins (fHbp) contained in the bivalent rLP2086 MenB vaccine. To date, experience with MEASURE has been lacking, and in a long-awaited article, McNeil et al. (mBio 9:e00036-18, https://doi.org/10.1128/mBio.00036-18), provide detailed mapping of a cross-reactive antibody binding epitope and explore the potential utility of MEASURE in predicting the susceptibility of individual MenB strains to antibody-mediated killing. Remaining questions center around why some strains with high fHbp expression are nonsusceptible to anti-fHbp antibody killing. Consideration of alternative methods, such as a standardized enzyme-linked immunosorbent assay (ELISA), might offer a more readily available and reproducible assay for wider use.